2016
DOI: 10.1111/jcpe.12531
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association between physical strength, obesity, periodontitis and number of teeth in a general population

Abstract: Periodontitis is associated with GS modified mainly by anthropometric measures related to adiposity and inflammation. Putative mechanisms encompass interactions of factors declining with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 33 publications
6
40
0
Order By: Relevance
“…found that a significant association between the number of teeth and handgrip strength disappeared after adjusting for confounders in 80‐year‐old participants. Our data show additional evidence by complementing elements that were not sufficiently addressed in previous studies …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…found that a significant association between the number of teeth and handgrip strength disappeared after adjusting for confounders in 80‐year‐old participants. Our data show additional evidence by complementing elements that were not sufficiently addressed in previous studies …”
Section: Discussionsupporting
confidence: 75%
“…No studies have reported the effect of the number of teeth on handgrip strength in Koreans. Considering that the association between the number of teeth and handgrip strength remains controversial, the results of this nationwide representative study are significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[24][25][26] Similarly, in a recent cross-sectional study that assessed peri-implant outcomes in obese and non-obese patients, 27 showed that increased body weight is a predisposing factor for poor peri-implant outcomes that is possibly modified by c-reactive protein (a proinflammatory biomarker). Several recent studies reported that increased BMI is a modifying risk factor for periodontal tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional open surgery has lots of complications with considerate influence to renal function. The elderly with low body reserve capacity, reduced tolerance to surgery, slow postoperative recovery may develop many complications as the result of prolonged bed rest after open surgery (6,7). In the past, limited by the hardware, kidney stones were treated by ESWL or PCNL with limited safety and efficacy (8).…”
Section: Introductionmentioning
confidence: 99%